Sing me a story! Tell me a song! - Hilda L. Jackman (Thomson/Delmar Learning, 2005)
Teachers, future teachers, day care providers and other professionals responsible for educating young children will be amazed at the wealth of valuable, well-organized, theme-based teaching material in Sing Me a Story! Tell Me a Song! It uses developmentally appropriate themes to integrate the curriculum of children from infancy to age eight. Thematic learning activities such as finger plays, poems, music and movement, and creative food experiences enable children to achieve curriculum goals, skills, and concepts. Activities for each of the 30 themes presented are designated as appropriate for infants, toddlers, preschoolers and kindergarteners, or primary-grade students using an icon to suggest appropriateness. Goals for each theme are written in a developmentally sequenced listing to aid planning for childrenÂ's ongoing development as they grow and learn